2020
DOI: 10.1111/and.13890
|View full text |Cite
|
Sign up to set email alerts
|

Novel predictive risk factor for Erectile Dysfunction: Serum folic acid

Abstract: Erectile dysfunction (ED) is defined as the persistent inability to attain or maintain an erection sufficient to permit satisfactory sexual activity (Hatzimouratidis et al., 2016). Penile erection is a complex neurovascular phenomenon, and ED may result from various abnormalities arising from vasculogenic, neurogenic, hormonal, anatomical, drug-induced and psychogenic causes (Zhengyan et al., 2014). Endothelial dysfunction (EDys) has been found to be central to atherosclerosis which is one of the most common c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…(2014) reported for the first time that serum FA levels in the ED group were significantly lower than those in the non‐ED group and suggested that FA deficiency might be one of the risk factors for ED. Several subsequent studies reported similar results and further suggested that the degree of FA deficiency was related to the severity of ED (Attia et al., 2019; Gupta et al., 2020; Karabakan et al., 2016). But recent cross‐sectional study of 1,381 participants found no significant difference in FA levels between ED patients and controls (Chen et al., 2019).…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…(2014) reported for the first time that serum FA levels in the ED group were significantly lower than those in the non‐ED group and suggested that FA deficiency might be one of the risk factors for ED. Several subsequent studies reported similar results and further suggested that the degree of FA deficiency was related to the severity of ED (Attia et al., 2019; Gupta et al., 2020; Karabakan et al., 2016). But recent cross‐sectional study of 1,381 participants found no significant difference in FA levels between ED patients and controls (Chen et al., 2019).…”
Section: Introductionmentioning
confidence: 65%
“…In four studies (Gupta et al., 2020; Karabakan et al., 2016; Sansone et al., 2018; Yan et al., 2014), there was no significant difference in age between the ED group and the non‐ED group. Meta‐analysis results showed that the FA level of the non‐ED group was significantly higher than that of the ED group, with low heterogeneity (MD = 3.24, 95% CI 2.15–4.34, p < 0.001, I 2 = 20%).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations